Customer care effectiveness and the performance of telecommunication industries in Nigeria - Alfred, Lydia; Edogbanya, Adejoh (2016)
This paper examined the importance of customer care unit, the retention of service users and the volatilities of Tele-communication companies in Nigeria.This paper attempt to find the relationship between customer service and the patronage of the service users of Telecommunication companies in Nigeria. This article is based on data obtained from survey and literature in the context of customer’s service delivery, marketing and customer’s retention. Recommendations were made amongst which are; provision of proper guidelines on customer service delivery, training and retraining of customer care representatives and taking into consideration the complaints by the service users and improving on the quality of service delivery.This recommendation is a result that marketing focuses on customer needs, want, preference, attitudes and lifestyles.